Mastery of academic writing for journal editors - Subrata, Sumarno Adi (Innovation in Health for Society, 2026)
The growing of scholarly publication in health demands that journal editors possess more than just subject-matter expertise in the field. They must demonstrate a mastery of academic writing to maintain the research integrity and impact of their publications. A well-written and well-presented article makes it easier for researchers to understand its content and increases the potential for higher citations. Therefore, it is important for journal editors to provide extra attention to every submitted manuscript, particularly those that have been accepted and are awaiting publication. At this present, articles discussing the urgency of academic writing mastery for editors remain scarce; thus, this editorial will address this gap by providing examples within the domain of health innovation. The editorial article explores the role of editors as both gatekeepers of knowledge and facilitators of scientific discourse. It argues that mastery for an editor involves a dual principle such as the technical ability to refine complex arguments for clarity and precision and the pedagogical insight required to provide constructive feedback to authors. The article identifies the basic competencies necessary for editorial process by looking at the current trends in peer review and manuscript preparation. These include a deep understanding of disciplinary conventions, the ability to identify subtle rhetorical shifts that affect the validity of claims, and a commitment to linguistic inclusivity in health innovation research. Furthermore, the discussion addresses how an editor’s mastery of structure and flow can significantly enhance a journal's citation impact and readability. The article suggests that formalizing writing mastery within editorial training programs is essential for those who deep dive into publication world. When editors function as master practitioners of the written word, they do more than simply process submissions. They elevate the quality of the writing to make sure that research is communicated with the transparency and power as it deserves. Keywords: Academic writing, editorial process, gaps analysis, Innovation in health, writing skills